PENGARUH ANONIMITAS DAN ONLINE DISINHIBITION TERHADAP KESEHATAN MENTAL POSITIF PADA PENGGUNA MEDIA SOSIAL (WHATSAPP, INSTAGRAM, FACEBOOK, TIK-TOK) - Hanifah, Ismi; Rozi, Fahrul (Psikologi UHAMKA, 2022)
This study aims to determine whether there is an effect of anonymity and online disinhibition on positive mental health. The subjects in this study were social media users (Whatsapp, Instagram, Facebook, TikTok) with an age range of 13-18 years, with a total of 117 respondents consisting of 30 men and 87 women. This study uses a quantitative research design that is distributed through an online questionnaire, using a purposive sampling technique. There are three instruments in this study, namely; (1) the anonymity scale was developed by Lee, Choi and Kim which was adapted from Chaerunnisa by using the dimensions developed by Pfitzmann and Hansen namely unlinkability, unobservability and pseudonymity to see the level of anonymity. Consists of 12 favorable items and 6 unfavorable items. (2) the online disinhibition effect scale that has been adapted from Farikhah by using aspects that affect online disinhibition proposed by John Suller namely Dissociative Anonymity, Invisibility, Asynchronicity, Solipsistic Introjection, Dissociative Imagination, and Authority Minimization. With the number of items as many as 29 favorite items. (3) the positive mental health scale developed by Lukat et al is composed of a combination of four mental health measuring tools which is then simplified into 9 statement items. The data analysis technique used in this research is the Multiple Linear Regression test. The results of the multiple linear regression analysis show the conclusion that there is a significant effect between anonymity and online disinhibition on positive mental health in social media users (Whatsapp, Instagram, Facebook, TikTok) with a probability value of 0.036 below 0.05 (P<0.05), and the coefficient of R square is 0.057. So this shows the contribution of anonymity and online disinhibition to positive mental health by 5.7% and 94.3% the contribution of other variables unknown to the researcher. The existence of this research is expected to contribute to the development of education related to positive mental health in individual social media users.